Describo el cambio de una magnitud con respecto al paso del tiempo - Garcia Garcia, Wily Orlando (2019)
The learning session entitled “Describo el cambio de una magnitud con respecto al paso del tiempo” (Describing how a magnitude changes as time goes by) belonging to the mathematic area was intended to the third-grade primary school class of Francisco de Zela school in El Porvenir district, Trujillo province, La Libertad region in Peru, 2019._x000D_ The teaching proficiency piece of work was developed with the problem-solving approach in three phases: In the plannig phase the learning evidence, the evaluation performance and evaluation instrument were taken into account. Besides, the didactic sequence applied to Mathematics by developing processes involving capacities to solve regularity, equivalence and change problems._x000D_ The second phase involves the theoretical support which includes the scientific and curricular contents that the student should build up during the leaning session in order to accomplish both the evidence and performance achievement._x000D_ Finally, in the third phase, the pedagogical support regarding the mathematical area includes the pedagogical processes, the didactical processes and the cognitive processes that students develop while they are working up their knowledge as well as the formative evaluation approach.which is present all along the processes.